1994
DOI: 10.1165/ajrcmb.11.3.7916196
|View full text |Cite
|
Sign up to set email alerts
|

Functional behavior of the beta-adrenergic receptor-adenylyl cyclase system in rabbit airway epithelium.

Abstract: Stimulation of adenylyl cyclase mediates the effects of beta-adrenergic agonists and prostaglandin E2 (PGE2) on tracheobronchial epithelial cell function by increasing intracellular cyclic adenosine monophosphate (cAMP). In turn, increases in cAMP affect airway function by modulating ciliary beating, chloride and water transport, mucus secretion, and release of bronchoactive substances. This study examined the function and regulation of the beta-adrenergic receptor-adenylyl cyclase system (beta AR-AC) in trach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…PDE inhibitor-␤ agonist synergism and PDE inhibitor class specificity requirements for the activation of chloride transport in CF-T43 cells. 36 Cl efflux rate is plotted as a function of time, and the addition of stimulatory compounds is indicated by the solid bar. Error bars represent SEM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PDE inhibitor-␤ agonist synergism and PDE inhibitor class specificity requirements for the activation of chloride transport in CF-T43 cells. 36 Cl efflux rate is plotted as a function of time, and the addition of stimulatory compounds is indicated by the solid bar. Error bars represent SEM.…”
Section: Resultsmentioning
confidence: 99%
“…In these experiments, chloride efflux appeared to be of larger magnitude when albuterol was used as an agonist, possibly indicating the involvement of ␤ 2 receptors in this process. Alternatively, this effect may be due to receptor desensitization known to occur with isoproterenol (36).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative explanation, the expression of I BE may have resulted from de novo generation of several kinds of membrane receptors including adenosine-and ␤-adrenergic receptors in bronchitis model epithelium. However, this possibility is remote because the normal rabbit epithelium isolated from trachea already possesses abundant ␤-adrenergic receptors and generates cAMP in response to ISO, epinephrine, or prostaglandin E 2 (20,21). Therefore, we assumed that I BE was evoked through a newly generated effector sensitive to a common cellular mechanism shared by ATP, ISO, and ADO.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this type of epithelium has been shown to have no Isc response to ␤ -agonists or agents that raise cellular cyclic adenosine 3 Ј ,5 Ј -monophosphate (cAMP) (13,14,19), although it possesses ␤ -adrenergic receptors as well as an ability to increase the cellular level of cAMP in the presence of epinephrine, isoproterenol, or forskolin (20,21). The electric refractoriness of the freshly isolated rabbit trachea to isoproterenol and other cAMP-mediated agents was also confirmed in our previous study, and extracellular ATP was found to elicit a transient increase in Isc that was carried by Cl Ϫ , probably via P 2u -receptor (22).…”
Section: Introductionmentioning
confidence: 99%